Access information wing in public institutions in the province of Huánuco - Romero Vela, Jorge (2017)
Free Access to Information includes access by any person; documentation consists of public records, minutes of meetings, correspondence, technical reports, scientific studies or any documentation financed by public budgets. This research sought to answer mainly to the following question: Why the fear of public authorities to provide information Huánuco its management in a transparent manner?, And the hypothetical answer: That the right to access information from the public in Huánuco is very limited, due to arbitrariness, fear and ignorance of the laws of the relevant authorities. To achieve verify this assumption, the research was carried out based on the following objective: To assess why the fear of public authorities to provide information Huánuco its management in a transparent. The methodological framework used was pure execution-type transverse cross-sectional descriptive design. Population, El Colegio de Abogados de Huánuco, has a pattern of registrations of over 3000 practitioners. Of that total, active professionals are approximately 1000 lawyers. The sample consisted of 5% of total assets lawyers in this case the sample is 50 firms. The main conclusions reached with this research were as follows: In the present research has found that most authorities and officials of various State agencies in our region know the legal framework on the right to access public information and that the vast majority of the population is generally unaware on the right of even reaching threequarters of citizens. That the Public Ministry and the Judiciary of Huánuco, not interested in administering justice on claims relating to access to information in public administration. That a majority 60% of government officials are afraid to provide transparent information due to a high degree of corruption, poor management and arbitrariness is 14% deficiency and lack of fitness and 14% due to ignorance of the law of transparency of information and, on average between 70 and 80% of the institutions of the region, hampering access to information. So clearly there is no transparency in the administration of any custodial institutions of Huánuco.